Young Australian women's accounts of smoking and quitting: a qualitative study using visual methods - Zoi Triandafilidis; Jane M. Ussher; Janette Perz; Kate Huppatz (BMC, 2018)
Abstract Background Although the overall rate of smoking in Australia continues to decline, the rate of decline has begun to slow. Rates of smoking among young women in Australia have been a particular concern, which has led to the development of targeted public health campaigns. Poststructuralist theory has successfully been used in research to explore the way in which young women experience smoking. However, there is an absence of poststructuralist analysis of young women's experiences of quitting. This study aims to address this gap. Methods We carried out 27 interviews with young Australian women smokers and ex-smokers. Eighteen of those women then participated in a photography activity and follow-up interviews. A Foucauldian discourse analysis of the data was conducted. Results Through our analysis, we identified three discourses: 'The irresponsibility of smoking: Quitting as responsible', 'The difficulties of quitting: Smoking as addictive', and 'Making a decision to quit: Smoking as a choice'. In relation to these discourses, participants took up contradictory positions of responsibility and resistance, addiction and agency. Taking up these positions had implications for young women's subjectivity, and the way they engaged with tobacco controls and cessation support. Conclusions The analysis highlights the complex and contradictory nature of young women's experiences with smoking and quitting. The study's findings are considered in relation to the improvement of tobacco control policies and cessation support programmes targeted at young women.